Design and Equipment Considerations for Organic Light Emitting Diodes Experiments - Xu, Luogen; Rybicki, James (My University, 2017)
The purpose of this study is to examine organic light emitting diodes (OLEDs) for new purposes in the optical technology field.
Color poster with text, images, graphs, and models.
Keywords: Optical technology; Electricity; Organic light emitting diodes (OLEDs); Posters